2022
DOI: 10.1186/s12870-022-03797-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated methylome and transcriptome analysis unravel the cold tolerance mechanism in winter rapeseed(Brassica napus L.)

Abstract: Background Cytosine methylation, the main type of DNA methylation, regulates gene expression in plant response to environmental stress. The winter rapeseed has high economic and ecological value in China's Northwest, but the DNA methylation pattern of winter rapeseed during freezing stress remains unclear. Result This study integrated the methylome and transcriptome to explore the genome-scale DNA methylation pattern and its regulated pathway of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Therefore, we propose that DNA methylation-mediated excessive ROS accumulation in 'NMC' disrupts intracellular ROS homeostasis during early embryo development, ultimately leading to seed abortion. Recent reports have highlighted the critical roles of DNA methylation-mediated ROS homeostasis in various aspects of plant development and stress response, including salt stress (Chen et al 2015 ; Hu et al 2021 ), heat stress (Ma et al 2018 ; Sakai et al 2022 ; Zhu et al 2021 ), chilling/freezing stress (Guo et al 2019 ; Zheng et al 2022 ), and fruit ripening (He et al 2020 ). Based on our findings, we suggest that DNA methylation-mediated ROS homeostasis also plays a role in seed development in litchi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we propose that DNA methylation-mediated excessive ROS accumulation in 'NMC' disrupts intracellular ROS homeostasis during early embryo development, ultimately leading to seed abortion. Recent reports have highlighted the critical roles of DNA methylation-mediated ROS homeostasis in various aspects of plant development and stress response, including salt stress (Chen et al 2015 ; Hu et al 2021 ), heat stress (Ma et al 2018 ; Sakai et al 2022 ; Zhu et al 2021 ), chilling/freezing stress (Guo et al 2019 ; Zheng et al 2022 ), and fruit ripening (He et al 2020 ). Based on our findings, we suggest that DNA methylation-mediated ROS homeostasis also plays a role in seed development in litchi.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in MSD , such as the oiwa mutant, disrupt ROS homeostasis, resulting in high ROS levels in the embryo sac and leading to sterility or arrested embryogenesis (Victoria Martin et al 2013 ). Recently, there have been reports highlighting the crucial roles of DNA methylation-mediated ROS homeostasis in various aspects of plant development and stress response, including salt stress (Chen et al 2015 ; Hu et al 2021 ), heat stress(Ma et al 2018 ; Sakai et al 2022 ; Zhu et al 2021 ), chilling/freezing stress(Guo et al 2019 ; Zheng et al 2022 ), and fruit ripening (He et al 2020 ). For instance, the application of 5-azaC, an inhibitor of DNA methyltransferase, has been found to enhance the rates of superoxide anion (O 2 − ) production, thereby contributing to the ripening of berry fruits (Guo et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Freezing stress responses are regulated by a complex interplay of genes and environmental factors, and involve a variety of physiological pathways [ 61 , 62 , 63 , 64 ]. In this study, we identified 12 pathways that included 16 DAMs and 65 DEGs through combined transcriptome and metabolome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, peach mealiness is another major issue of CI, which highly reduces consumer acceptance and market value. The related epigenetic mechanisms have been recently discovered: 144 mCHH-DMRs amounted most both in normal and mealy fruit after 30-day storage at 0 °C and most DMRs were not de novo developed during the cold storage, they just underwent changes of methylation degree. Further, the potential mealiness-regulating candidates, Cytochrome P450 82A (CYP82A) and UDP-arabinose 4 Epimerase 1 (UA4E1), were expression-downregulated and promoter-hypermethylated in mealy fruit.…”
Section: Volatile Organic Compounds (Vocs) and Cold Storage With Chil...mentioning
confidence: 99%